Bildung and subject didactics: exploring a classical concept for building new insights - Schneuwly, Bernard; Vollmer, Helmut Johannes (European educational research journal EERJ, 2018)
In the beginning of the 19th century, Humboldt defined Bildung as both process and product of the developing person. In this contribution we discuss how this classical concept may be used for defining subject didactics. We use two complementary approaches to answer it: a historical analysis, and the construction of a theoretical model. 1) Presenting results of a historical research on the process of didactic transposition of grammar in the 19th century, we show that Bildung seems to function as one driving force among others. 2) In reflecting on the respective signification of “learning” on the one hand and “Bildung” on the other hand, it is possible to define three levels of outcomes which (school) subjects have on persons who learn, Bildung being a not necessarily intended, but potential one. Both approaches show that Bildung is indeed a concept that can be used for doing research in subject didactics and for conceiving them as a whole, with a common core and with many differences between individual subject didactics at the same time.